Barriers and facilitators to access mental health services among people with mental disorders in Indonesia: A qualitative study - Lafi Munira; Pranee Liamputtong; Pramon Viwattanakulvanid (Belitung Raya Foundation, Indonesia, 2023)
Background: The care and treatment management of people with mental health problems has become a prominent global concern in recent years that requires consistent attention. However, the literature suggests that only a small percentage of individuals with mental health problems in Indonesia receive the necessary mental health care. Therefore, it is crucial to explore this gap. Objective: This study aimed to explore barriers and facilitators that affect access to mental health services among people with mental health disorders in Indonesia. Methods: The study employed a qualitative descriptive design and focused on individuals with depression, anxiety, or bipolar disorder. Data were collected through in-depth interviews conducted via WhatsApp chat with 90 participants aged 18-32, who were purposively selected from Sumatra, Java, Kalimantan, and Papua Islands in Indonesia between January and June 2022. Thematic analysis was used to analyze the data. Results: The barriers to accessing mental health services included: 1) uneasy access to mental healthcare facilities, 2) stigma, lack of social support, and delay in receiving proper treatment, and 3) expensive treatment costs without national health insurance membership. Importantly, the facilitators to access mental health services included: 1) national health insurance membership, 2) support from spouse, family, and closest friends and its association with mental health literacy, and 3) self-help. Conclusion: The widespread distribution of mental health knowledge is recommended among healthcare providers, including public health practitioners and primary care nurses, to enhance their mental health literacy and competencies while rendering services to individuals with mental disorders. Additionally, efforts should be made to educate and promote awareness among caregivers and communities to reduce the stigma faced by those with mental disorders.